Adding Fairness to Order: Preventing Front-Running Attacks in BFT Protocols using TEEs - Stathakopoulou, Chrysoula; Schwarz-Rüsch, Signe; Brandenburger, Marcus; Vukolić, Marco (40th International Symposium on Reliable Distributed Systems (SRDS 2021), 2021)
This paper presents Fairy: a modular system that augments any Total Order Broadcast (TOB) protocol with fairness properties, namely input (request) causality and sender obfuscation. With these properties, Fairy helps to prevent front-running attacks where an adversary can interfere with the order of requests depending on request payload and sender identity, allowing for substantial application-level consequences. Fairy leverages Trusted Execution Environments (TEEs) to implement fairness on top of a TOB-based ordering service. Fairy collocates TEEs with ordering service nodes effectively making them run as trusted proxies of actual TOB clients. TEEs help Fairy to achieve both input causality and sender obfuscation — previous related systems addressing only input causality. We evaluate Fairy on top of a recent, efficient Byzantine FaultTolerant (BFT) TOB protocol and compare it to state-of-the-art BFT TOB with input causality. We show that Fairy improves state-of-the-art throughput by 66% and reduces latency by 50%.<br
Keywords: total order broadcast; trusted execution; frontrunning attacks